2002
DOI: 10.1191/0959683602hl525rr
|View full text |Cite
|
Sign up to set email alerts
|

Environmental variability within the Chinese desert-loess transition zone over the last 20000 years

Abstract: The desert/loess transition zone in northern China is sensitive to climate variability, which is controlled mainly by the relative strengths of the East Asian summer and winter monsoons. Sandy loess layers found in the Loess Plateau and palaeosol sequences found in the sandy desert demonstrate latitudinal shifts of the southern desert margin over the last 20 000 years. Stratigraphic investigations together with radiocarbon and some thermoluminescence dating, show that during the last glacial maximum the desert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
2

Year Published

2002
2002
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(40 citation statements)
references
References 18 publications
1
37
2
Order By: Relevance
“…There is a general agreement that the deserts exhibited a major northwestward contraction compared to their modern distribution. Nevertheless, there are some differences in detail: for example, for the mid-Holocene, Zhou et al [2002] demonstrated that the southern desert margin shifted about 3°in latitude northward (to 41°N) (green dashed line in Figure 4); Jin et al [2001] suggested that the desert/loess boundary moved about 250 km westward (pink dashed line in Figure 4); Dong et al [1997] consider that the desert/loess boundary belt shifted northwestward to near the modern 200-300 mm annual isohyet (dark purple dotted line in Figure 4), and Lu et al [2013] suggested that the East Sandy Land was almost completely stabilized and exhibited a major retreat while the margin of the West Desert exhibited a smaller change (blue dashed line in Figure 4). …”
Section: 1002/2014gl059952mentioning
confidence: 99%
“…There is a general agreement that the deserts exhibited a major northwestward contraction compared to their modern distribution. Nevertheless, there are some differences in detail: for example, for the mid-Holocene, Zhou et al [2002] demonstrated that the southern desert margin shifted about 3°in latitude northward (to 41°N) (green dashed line in Figure 4); Jin et al [2001] suggested that the desert/loess boundary moved about 250 km westward (pink dashed line in Figure 4); Dong et al [1997] consider that the desert/loess boundary belt shifted northwestward to near the modern 200-300 mm annual isohyet (dark purple dotted line in Figure 4), and Lu et al [2013] suggested that the East Sandy Land was almost completely stabilized and exhibited a major retreat while the margin of the West Desert exhibited a smaller change (blue dashed line in Figure 4). …”
Section: 1002/2014gl059952mentioning
confidence: 99%
“…This shows that climatic oscillations may have a very different expression in eastern Asia than the "cold, dry" North Atlantic younger Dryas event [25]. These effects in China appear to be controlled by changes to the flow of monsoonal precipitation [21,22,27]. There is increasing evidence that these local effects may also occur in many different parts of the world.…”
Section: Correlations Of Climatic Data In Chinese Loess Depositsmentioning
confidence: 99%
“…Shi (2005) used an assemblage of tools found in ancient sites to deduce the activities of past subsistence economies, which were then compared with the findings of environmental studies. W. Zhou et al (2002), Song and Zhang (2001), and Ren (2000b) gathered environmental data in the southwest region of Northeast China in an attempt to determine whether human activities had caused deforestation and desertification during prehistoric times. All these studies are indicative of major achievements in the development of environmental archaeology in Northeast China.…”
Section: History and Recent Developmentsmentioning
confidence: 99%